MODELING OF FORWARDER PRODUCTIVITY AND COSTS IN THINNED PINE STANDS - Rodrigues, Carla Krulikowski; Lopes, Eduardo da Silva; Filho, Afonso Figueiredo; da Silva, Matheus Kaminski Cândido (Floresta, 2018)
Abstract The aim of this study was to assess the influence of some operational variables on the forwarder productivity and production cost in thinned Pinus taeda L. stands by means of mathematical modeling. This study was carried out in a forest company located at Quedas do Iguaçu, state of Paraná, Brazil. Two stands at 9 and 10 years old from sites with high productivity and similar soil and relief features were studied. A time-motion study was applied to determine the operational cycle time, operational efficiency, productivity, and production costs. By means of mathematical modeling, we verified the influence of the variables: age of stand; cycle time; load volume; and extraction distance on the forwarder productivity and production costs. Models were fitted for estimating the forwarder productivity using cycle time, load volume, and extraction distance. Thus, we obtained the determination adjusted coefficients of 0.88 and 0.94, with an estimate standard error between 6.9% and 13.5%. Models for estimating production cost through the load volume variable presented a determination coefficient of 0.64 and 0.86, with an estimate standard error of 23.1% and 26.7%. Such results have shown the possibility of using mathematical models to estimate the performance of forest machines as a tool for planning the timber harvesting operations.